PROMOSI MUSEUM ADITYAWARMAN MELALUI MEDIA INFORMAS - Shiva, Ridho Ibnu; Zalmi, Fadhila Nurul Husna; Hasfera, Dian (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
Despite being an important cultural destination in West Sumatra, the Adityawarman Museum is still not optimal in its promotion and marketing efforts, resulting in low tourist visits. This qualitative research with a case study approach aims to explore the promotional strategy of the Adityawarman Museum through the use of information media, particularly virtual tour videos. Examining the concept of promoting information institutions such as implementing the right promotional mix, building a positive image, and utilizing the latest media and technology, this research emphasizes the importance of presenting attractive and informative visual content to attract public interest. Through observation, in-depth interviews with museum managers and tourism stakeholders, as well as literature studies, the research results show great opportunities in utilizing virtual tour videos as the main promotional media for the Adityawarman Museum. Virtual tour videos allow the public to experience visiting the museum virtually, exploring the museum's collections and facilities interactively. This strategy involves developing quality video content with engaging narratives, visualization of featured collections, and virtual guidance by competent museum guides. In addition, the promotional strategy should also involve collaboration with various tourism stakeholders to reach a wider audience. In conclusion, virtual tour videos have great potential in effectively promoting the Adityawarman Museum, increasing awareness, encouraging actual visits to the museum, and building a positive image of the institution through an engaging and informative virtual experience.